ダイ 5 ジ ナンキョク エットウ タイイン 16 ニン ノ シュウダン セイカツ ニ カンスル 2・3 ノ コウサツ - 松田, 達郎; マツダ, タツロウ; MATSUDA, Tatsuro (国立極地研究所, 1964)
P(論文) The writer tried to investigate the social life of the wintering party of the 5th Japanese Antarctic Research Expedition. 1. The relation between the kinds of recreation or play of the wintering members and their working hours was studied. The members having night duty had less kinds of recreation or play than the other members. 2. The words in vogue were recorded and their origins were analysed. It was known that the word in vogue originated mainly from the favorite saying or a slip of the tongue made by a party member. 3. The nickname related to the age of the party member. The youger members were apt to be called frequently by their nicknames. 4. It was recognized that at meals the age of the member and his working hours related to the sitting position at table. The position of the member was generally arranged in the order of the age of the member and it was noted that the position of the member having night duty was not stable. 5. Psychological experiment was tried by food-test. The cakes or confections sufficiently prepared on the table were taken casually by about 45% of party members who happened to be present at tea time. departmental bulletin paper